ChemInform Abstract: Pericyclic [4 + 2] and [3 + 2] Cycloaddition Reactions of Nitroarenes in Heterocyclic Synthesis. Issue 35 (8th August 2013) - Shevelev, S. A.; Starosotnikov, A. M.
Abstract Review: 93 refs.